Is Apocalyptic Kiev Still Apocalyptic Kiev in English Translations of Mikhail Bulgakov's Novel The White Guard? - Petra Žagar-Šoštarić; Natalia Kaloh Vid ([sic])
The White Guard, an epic narrative on the Russian Civil War, is also an urban novel based on the author’s personal experiences in Kiev during the tumultuous years of the Revolution and Civil War. Following the traditions established by F. Dostojevsky and I. Bunin, Bulgakov introduces the City, Kiev, not only as the setting of the novel, but as one of the main protagonists – one that changes, develops and takes part in the lives of the other protagonists. The city is thus transformed into a psychological dimension where the violence of war and the mental world of the characters are reflected onto the city itself. As intertextuality is one of the main characteristics of Bulgakov’s style, he employs numerous allusions to the Book of Revelation when describing the events in the novel and when constructing the image of the city. Following his typical ambivalence, Bulgakov depicts Kiev as a place of beauty, light, and happiness, similar to the New Jerusalem from the Revelation, and as a place of chaos, promiscuity, and violence, like that of the apocalyptic Babylon. The city is also divided into two zones: the Civil war zone, dangerous and violent, and a domestic zone, which represents safety, family and old prerevolutionary values. The novel has been translated into English three times: by Michael Glenny (1971), Marian Schwartz (2008) and Roger Cockrell (2012). This unique material offers thorough insight into translation shifts, not only from a synchronic, but also from a diachronic perspective. In our research, we focused on the translation strategies used when rendering apocalyptic allusions employed by the author to describe the City and assessed some of translation choices. We wonder if and to what extent the translators recognized and adequately transferred the original allusions and the ambivalent, apocalyptic and complex world of Bulgakov’s City.